Prognostic factors associated with recurrent COVID-19 and impact of SARS-CoV-2 vaccine on patients with chronic lymphocytic leukemia - Pepe, Sara; Mazzarella, Roberta; Andriola, Costanza; Soriano, Tania; Sforzini, Giorgio; Mauro, Francesca Romana (Frontiers in Oncology, 2026)
IntroductionPatients with chronic lymphocytic leukemia (CLL) are highly vulnerable to infections owing to persistent immune dysfunction, leading to an increased risk of severe disease and reinfection.MethodsWe conducted a retrospective study of 210 CLL patients managed at the Hematology Unit, Sapienza University of Rome, who survived an initial SARS-CoV-2 infection between March 2020 and December 2024. The aim of this study was to assess the incidence, clinical course, and predictors of subsequent COVID-19 events during the Omicron-dominant period.ResultsA subsequent COVID-19 occurred in 71 patients (33.8%), diagnosed after a median of 14 months (IQR, 9–20) from the first episode. Reinfections were significantly more frequent in patients who had experienced their first infection before the Omicron wave (47% vs. 30%; p = 0.039). Compared with the initial event, subsequent COVID-19 was milder, with lower rates of pneumonia (8.4% vs. 22.7%; p = 0.008), hospitalization (8.4% vs. 25.4%; p = 0.002), and no COVID-19–related deaths. Patients on active CLL treatment and those with a Cumulative Illness Rating Scale score ≥6 were at significantly higher risk of reinfection. In multivariate analysis, ongoing CLL therapy (HR 1.92; 95% CI: 1.17–3.16; p = 0.010) and elevated comorbidity burden (HR 2.20; 95% CI: 1.30–3.71; p = 0.003) independently predicted reinfection. SARS-CoV-2 vaccination did not significantly prevent new infections (36% vs. 33%; p = 0.638), but booster doses were associated with prolonged reinfection-free survival (16.3 vs. 9.3 months; p = 0.001). These findings indicate that SARS-CoV-2 reinfections remain common but generally mild among CLL patients in the Omicron era. High comorbidity burden and active therapy increase reinfection risk, while booster vaccination may extend protection intervals. Vaccination boosters are essential to reduce COVID-19 morbidity in this immunocompromised population.